ANGPTL3 deficiency associates with the expansion of regulatory T cells with reduced lipid content. (December 2022) - Pinzon Grimaldos, Alessandra; Pacella, Ilenia; Bini, Simone; Tucci, Gloria; Cammarata, Ilenia; Di Costanzo, Alessia; Minicocci, Ilenia; D'Erasmo, Laura; Arca, Marcello; Piconese, Silvia
Abstract: Background and aims: Angiopoietin-like 3 (ANGPTL3) regulates lipid and glucose metabolism. Loss-of-function mutations in its gene, leading to ANGPTL3 deficiency, cause in humans the familial combined hypolipidemia type 2 (FHBL2) phenotype, characterized by very low concentrations of circulating lipoproteins and reduced risk of atherosclerotic cardiovascular disease. Whether this condition is accompanied by immune dysfunctions is unknown. Regulatory T cells (Tregs) are CD4 T lymphocytes endowed with immune suppressive and atheroprotective functions and sensitive to metabolic signals. By investigating FHBL2, we explored the hypothesis that Tregs expand in response to extreme hypolipidemia, through a modulation of the Treg-intrinsic lipid metabolism. Methods: Treg frequency, phenotype, and intracellular lipid content were assessed ex vivo from FHBL2 subjects and age- and sex-matched controls, through multiparameter flow cytometry. The response of CD4 T cells from healthy controls to marked hypolipidemia was tested in vitro in low-lipid culture conditions. Results: The ex vivo analysis revealed that FHBL2 subjects showed higher percentages of Tregs with a phenotype undistinguishable from controls and with a lower lipid content, which directly correlated with the concentrations of circulating lipoproteins. In vitro, lipid restriction induced the upregulation of genes of the mevalonate pathway, including those involved in isoprenoid biosynthesis, and concurrently increased the expression of the Treg markers FOXP3 and Helios. The latter event was found to be prenylation-dependent, and likely related to increased IL-2 production and signaling. Conclusions: Our study demonstrates that FHBL2 is characterized by high Treg frequencies, a feature which may concur to the reduced atherosclerotic risk in this condition. Mechanistically, hypolipidemia may directly favor Treg expansion, through the induction of the mevalonate pathway and the prenylation of key signaling proteins. Graphical abstract: Image 1 Highlights: In ANGPTL3 deficiency, hypolipidemia correlates with Treg expansion. Tregs from these individuals contain less intracellular lipids. In vitro, lipid deprivation induces the mevalonate pathway and Treg markers. Such event is prenylation-dependent and IL-2/CD25-related.